Sculpture in the Open Air : London County Council - Exhibition 1960. - James, Philip; Stamp, A. Reginald (London : London County Council, 1960)
Adams, Robert ; Armitage, Kenneth ; Arp, Hans (Jean) ; Batten, Mark ; Bloc, André ; Brown, Ralph ; Butler, Reg ; Caro, Anthony ; Chadwick, Lynn ; Charoux, Siegfried ; Clatworthy, Robert ; Claughton, R.B. ; Colvin, Marta ; Dalwood, Hubert ; Dow, Harold ; Durst, Alan ; Epstein, Jacob ; Etienne-Martin ; Frink, Elisabeth ; Gerrard, A.H. ; Gordine, Dora ; Hepworth, Barbara ; Ipousteguy, Jean ; Kennington, Eric ; King, Peter ; Lambert, Maurice ; Ledward, Gilbert ; McWilliam, F. E. ; Meadows, Bernard ; Moore, Henry ; Nimptsch, Uli ; Paolozzi, Eduardo ; Picasso, Pablo ; Richier, Germaine ; Skeaping, John R. ; Stahly, François ; Turnbull, William ; de Vasconcellos, Josephina ; Vogel, Karel ; Wheeler, Charles ; Zadkine, Ossip
biografie
Sculpture in the Open Air : London County Council - Exhibition 1960, Battersea Park, May to September 1960
Engels
boek